DAMPAK PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA LEMBAGA KESEHATAN CUMA-CUMA DOMPET DHUAFA) - Hemmy Fauzan; Bahrul Yaman; Eka Rulianti Putri (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2019)
This study will look further at how the effects or effects of career development and motivation on employee performance at the Dompet Dhuafa Free Health Institution (LKC). The problem that underlies why this research is conducted is because of employee dissatisfaction with the management of LKC Dompet Dhuafa related to the opportunity to get a job promotion so that it causes deviations in employee behaviour at his workplace. The method used in this research uses multiple linear analysis techniques. This multiple linear analysis is used to see or measure the extent of the influence of independent variables consisting of; career development and motivation, on the dependent variable represented by employee performance. In conducting its analysis, this study also uses SPSS 16.0 software with a total of 54 employees from the Dompet Dhuafa Free Health Institution (LKC). The results of this study indicate that career development has a significant influence on employee performance; this is indicated by the efficiency variable where career development has a positive influence of 0.383 and sig. 0,000 <0,10. Likewise important motivation for employee performance, this is indicated by efficiency variables where motivation has a positive effect of 0.212 and sig. 0.011 <0.10. This study also shows that the relationship between career development and motivation has a simultaneously significant influence on employee performance, based on the results of the test of determination of 0.573 or 57.3%, while other factors influence the remaining 42.7%. This also shows the results of the f test with the efficiency of career development and the motivation variable has a positive effect of 36,611 and a sig value of 0,000 <0,10.